Rancang Bangun Robot Autonomus Pembersih Kolam Ikan Hias - Adi, Mhd Adi Setiawan Aritonang; Kevin Antony; Luki Hernando; Deosa Putra Caniago (LPPM-ITEBA, 2024)
The importance of maintaining the cleanliness of ornamental fishponds in the context of urban life has been on the rise, especially as people's busy schedules often lead them to overlook the routine maintenance of their fishponds. One viable solution is the adoption of autonomous robot technology as a means of cleaning ornamental fishponds. This research aims to conduct a comprehensive evaluation of the design and implementation of an autonomous robot as a pond cleaner. The research method employed is quantitative, measuring outcomes and efficiency in numerical terms, with experimentation serving as the primary approach for data collection. Data collected is measured using tools such as a stopwatch, encompassing the time taken by the robot to complete its tasks, the time required to activate all components (approximately 10 seconds), and the time needed to clean the pond (around 4-5 minutes). The findings of this study enable us to assess the efficiency and effectiveness of autonomous pond cleaning robots in maintaining the cleanliness of fishponds.